TRITERPENES FROM CERIOPS DECANDRA (GRIFF.) W. THEOB. - Perez, Judy; Shen, Chien-chang; Ragasa, Consolacion Y (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: To isolate and identify the chemical constituents of Ceriops decandra. Methods: The chemical constituents of C. decandra (Griff.) W. Theob. were isolated by silica gel chromatography. The structures of the isolated compounds were identified by nuclear magnetic resonance (NMR) spectroscopy. Results: Chemical investigation of the dichloromethane extracts of the leaves of C. decandra has led to the isolation of 3Î²-E-coumaroylbetulinic acid (1), lupeol fatty acid esters (2), betulonic acid (3), betulin (4), betulinic acid (5), lupeol (6), lupenone (7), and a mixture of 3Î²-E-feruloyllupeol (8) and 3Î²-Z-feruloyllupeol (9), and chlorophyll a (10). The structures of 1-10 were identified by comparison of their NMR data with literature data. Conclusion: To the best of our knowledge, this is the first report on the isolation of 1-3 from C. decandra. Literature search revealed that the triterpenes isolated from C. decandra exhibited anticancer properties.